Association of Dual Sensory Impairment with Incident Mobility and ADL Difficulty. (17th December 2021) - Gendron, Colby; Armstrong, Nicole; Teixeira, Camila Vieira Ligo; Brenowitz, Willa; Lin, Frank; Swenor, Bonnielin; Jones, Richard; Simonsick, Eleanor
Abstract: Hearing and vision impairment are each independently associated with incident mobility disability and disability in activities of daily living (ADL). Whether dual sensory impairment (DSI) in both hearing (pure-tone average >25 dB) and vision (impaired visual acuity and/or impaired contrast sensitivity) is associated with greater risk of incident mobility and ADL difficulty, as compared to single or no sensory impairments, has not been well-studied. To examine these associations, we used data from 2, 020 Health Aging and Body Composition Study participants aged 70-79 years without mobility limitations. Incident mobility difficulty was defined as the first instance of a lot of problems or inability to walk ¼ mile and/or climb 10 steps, and incident ADL difficulty was defined as the first instance of problems with any ADL. Cox proportional hazards models adjusted by demographic covariates, diabetes, hypertension, and depressive symptoms were used to model these associations. Approximately 22.7% of the study had DSI. DSI was associated with increased risk of both incident mobility (Hazard Ratio [HR]=2.43, 95% Confidence Interval [CI]: 1.60, 3.69) and ADL difficulty (HR=2.39, 95% CI: 1.60, 3.56). Vision impairment only was associated with risk of incident mobility difficulty (HR=1.74, 95% CI: 1.09, 2.78), but not incident ADL difficulty (HR=1.45, 95% CI: 0.91, 2.32). Hearing impairment only was not associated with risk of either outcome. Synergistic effects of DSI on the additive scale were present. Sex and race did not modify associations. Monitoring of DSI may be beneficial in delaying incident difficulty.